2013
DOI: 10.5194/hessd-10-1041-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracing groundwater salinization processes in coastal aquifers: a hydrogeochemical and isotopic approach in Na-Cl brackish waters of north-western Sardinia, Italy

Abstract: In the Mediterranean area the demand of good quality water is often threatened by salinization, especially in coastal areas. The salinization is the result of concomitant processes due to both marine water intrusion and rock-water interaction, which in some cases are hardly distinguishable. In northwestern Sardinia, in the Nurra area, salinization due to marine water intrusion has been recently evidenced as consequence of bore hole exploitation. However, the geology of the Nurra records a long history f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Typically, spatial variations in salinity (or total dissolved solids) reflect the groundwater salinization characteristics and process (Cary et al, ; Mongelli, Monni, Oggiano, & Paternoster, ; Xie, Wang, Li, Su, & Duan, ). Tóth's groundwater flow theory demonstrates that the hydrogeochemical characteristics of groundwater in discharge areas of different hierarchical flow systems vary with residence time and environmental conditions (Bouchaou et al, ; Tóth, ; Wang, Jiang, Wan, Han, & Guo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, spatial variations in salinity (or total dissolved solids) reflect the groundwater salinization characteristics and process (Cary et al, ; Mongelli, Monni, Oggiano, & Paternoster, ; Xie, Wang, Li, Su, & Duan, ). Tóth's groundwater flow theory demonstrates that the hydrogeochemical characteristics of groundwater in discharge areas of different hierarchical flow systems vary with residence time and environmental conditions (Bouchaou et al, ; Tóth, ; Wang, Jiang, Wan, Han, & Guo, ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of karst aquifers in the Mediterranean area also relates to locally specific climatic conditions characterized by long, dry and hot summers (Fiorillo and Stevanovic 2015). According to Khaska et al 2013, the salinity of the Mediterranean coastal aquifers has been attributed to: (1) modern seawater intrusion (PulidoLeboeuf et al 2003(PulidoLeboeuf et al , 2004de Montety et al 2008;Carol et al 2009;Kouzana et al 2009;Schiavo et al 2009); (2) contributions of deep saline waters, which are usually warmer and derived from fossil seawater that have evolved through water-rock interactions (Schmerge 2001;Aquilina et al 2002;Hébrard et al 2006;Duriez et al 2007);and (3) water-rock interactions with Triassic evaporites (Mongelli et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The hydro-chemical characteristics of groundwater and stable isotopes (δ O and δ 2 H) have been used to identify groundwater origin and dynamics. Many studies revealed that there are close relations between the stable isotopes and other hydro-chemical properties of groundwater (Arslan et al 2012;Bahir et al 2018;Isawi et al 2016;Jahnke et al 2019;Lin et al 2011;Mongelli et al 2013).…”
Section: Introductionmentioning
confidence: 99%